Ikaros prevents autoimmunity by controlling anergy and Toll-like receptor signaling in B cells - Schwickert, T; Tagoh, H; Schindler, K; Fischer, M; Jaritz, M; Busslinger, M (Nature Research, 2019)
The establishment of a diverse B cell antigen receptor (BCR) repertoire by V(D)J recombination also generates autoreactive B cells. Anergy is one tolerance mechanism; it renders autoreactive B cells insensitive to stimulation by self-antigen, whereas Toll-like receptor (TLR) signaling can reactivate anergic B cells. Here, we describe a critical role of the transcription factor Ikaros in controlling BCR anergy and TLR signaling. Mice with specific deletion of Ikaros in mature B cells developed systemic autoimmunity. Ikaros regulated many anergy-associated genes, including Zfp318, which is implicated in the attenuation of BCR responsiveness by promoting immunoglobulin D expression in anergic B cells. TLR signaling was hyperactive in Ikaros-deficient B cells, which failed to upregulate feedback inhibitors of the MyD88-nuclear factor κB signaling pathway. Systemic inflammation was lost on expression of a non-self-reactive BCR or loss of MyD88 in Ikaros-deficient B cells. Thus, Ikaros acts as a guardian preventing autoimmunity by promoting BCR anergy and restraining TLR signaling.